A model for continuing professional development (CPD) in occupational therapy in South Africa: an adult education perspective - Collender, Monique Joeylene (University of the Free State, 2011)
In this research project, an in-depth study was done by the researcher with a view to compiling a model for Continuing Professional Development (CPD) in Occupational Therapy in South Africa from an adult education perspective. The Health Professions Council of South Africa (HPCSA) encourages CPD providers to offer learning activities in line with adult education principles and greater learner involvement, with the goal of not only acquiring new information or updating knowledge, but also of improving competence and ultimately the performance of the health professional with an end benefit to the patient/client. The problem that was addressed is the lack of a model for CPD in Occupational Therapy in South Africa. The overall goal of the study was to make a contribution to the effective and efficient implementation of the CPD system for occupational therapists in South Africa through identifying the CPD needs of occupational therapists and ultimately supporting health care in South Africa through education. The aim of the study was to develop a model for CPD in Occupational Therapy. It was, therefore, necessary to determine the needs for CPD of occupational therapists registered with the HPCSA with regard to content, cost, time, CPD activities, learning situations and mode of delivery in order to improve the effectiveness and efficiency of CPD programmes for the therapists if necessary. An embedded mixed-methods design was used – a design in which one data set provides a supportive, secondary role in a study based primarily on the other dataset. The methods that were used and which formed the basis of the study comprised a literature review, and – as the empirical study - a questionnaire survey and a Delphi process. The purpose of the literature review was to provide a background in order to develop the questionnaires and the context for the research problem, to establish the need for the research and to indicate that the researcher was knowledgeable about the area. The literature review focussed on CPD from an adult education perspective. The purpose of the questionnaire was to do a needs analysis of CPD for occupational therapists and to determine the effectiveness of CPD activities concerning the acquisition of new skills, knowledge and professional behaviour. The development of the questionnaire was also structured in such a way as to provide both quantitative and qualitative responses from the occupational therapists. The purpose of the Delphi technique was to evaluate the criteria that could be used to compile a model for CPD. A modified Delphi process was used. Three rounds of the Delphi process were required in the present study. The panel of experts were requested to rate, rephrase and comment on the statements. The premises and points of departure for the development of the model were outlined in addition to the benefits. The needs to be addressed by such a model received attention, together with the academic and administrative aspects for the compilation of the model. Challenges regarding the delivery, as well as recommendations made with regard to the model were provided. The study was done to make a contribution to the continuous effective and efficient implementation of the CPD system for occupational therapists in South Africa, through identifying the CPD needs of occupational therapists and ultimately supporting health care in South Africa through education. The study could also serve as a directive for higher education institutions, for not all undergraduate and post-graduate programmes and curricula are necessarily built on adult learning principles. It might especially be the case in professional disciplines that the findings of the study could help bridge shortcomings in this regard. The researcher is of the opinion that the research made a contribution to new knowledge. By developing the model the identified gap is bridged. The sound research approach and methodology ensured the quality, reliability and validity of the research. The completed research can form the basis for a further research agenda. Introduction of the model will encourage CPD providers to offer learning activities in line with adult education principles and greater learner involvement, with the goal of not only acquiring new information or updating knowledge, but also improving competence and ultimately the performance of health professionals with an end benefit to the patient.

Die navorser het tydens hierdie projek ‘n in diepte studie uitgevoer met die oog daarop om ‘n model saam te stel vir Voortgesette Professionele Ontwikkeling (VPO) in Arbeidsterapie in Suid-Afrika vanuit ‘n volwasse-onderwysperspektief. Die Gesondheidsberoeperaad van Suid-Afrika (GBRSA) moedig VPO-verskaffers aan om leeraktiwiteite aan te bied wat in ooreenstemming is met onderwysbeginsels en groter leerderbetrokkenheid, met die oog daarop om nie net nuwe inligting in te win of kennis by te werk nie, maar ook om vaardigheid en eindelik die prestasie van die professionele gesondheidswerker te verbeter, met ‘n eindvoordeel aan die pasiënt/kliënt. Die probleem wat aandag geniet het, was die gebrek aan ’n model vir VPO in Arbeidsterapie in Suid-Afrika. Die oorhoofse doel van die studie was om ‘n bydrae te maak tot die doeltreffende en doelmatige implementering van die VPO-stelsel vir arbeidsterapeute in Suid-Afrika deur die identifisering van die VPO-behoeftes van arbeidsterapeute en uiteindelik ondersteuning van gesondheidsorg in Suid-Afrika deur middel van onderwys. Die oogmerk met die studie was om ‘n model vir VPO in die Arbeidsterapie te ontwikkel. Dus was dit nodig om, indien nodig, die behoeftes rakende inhoud, koste, tyd, VPO-aktiwiteite, leersituasies en vorm van aflewering vir VPO vir arbeidsterapeute wat by die GBRSA geregistreer is, vas te stel ten einde die doeltreffendheid en doelmatigheid van VPO-programme vir terapeute te verbeter. Daar is van ‘n ingebedde gemengde-metodeontwerp gebruik gemaak – ‘n ontwerp waarin een datastel ‘n ondersteunende, sekondêre rol speel in ‘n studie wat primêr op die ander datastel gebaseer is. Die metode wat gebruik is en wat die grondslag van die studie gevorm het, het bestaan uit ‘n oorsig – as empiriese studie – ‘n vraelysopname en ‘n Delphi-proses. Die doel van die literatuuroorsig was om ‘n agtergrond te verskaf ten einde die vraelyste en die konteks vir die navorsingsprobleem te onwikkel, om die behoefte vir die navorsing te bepaal en om aan te dui dat die navorser oor kennis beskik ten opsigte van die veld. Die literatuuroorsig het gefokus op VPO vanuit ‘n volwasseonderwysperspektief. Die doel van die vraelys was om ‘n behoefteontleding te doen van VPO vir arbeidsterapeute en om die doeltreffendheid van VPO-aktiwiteite rakende die aanleer van nuwe vaardighede, kennis en professionle optrede te bepaal. Die ontwikkeling van die vraelys is ook sodanig gestruktureer om sowel kwalitatiewe as kwantitatiewe response van arbeidsterapeute te verskaf. Die doel van die Delphitegniek was om die kriteria wat gebruik sou kon word om ‘n model vir VPO saam te stel, te evalueer. ’n Aangepaste Delphi-proses is gebruik. Drie rondtes van die Delphiproses is genoodsaak in die huidige studie. Die paneel kundiges is versoek om die stellings te evalueer, herbewoord en om daarop kommentaar te lewer. Die veronderstellings en vertrekpunte vir die ontwikkeling van die model is, bykomstig tot die voordele, uiteengesit. Die behoeftes waarin deur so ‘n model voorsien moet word, het aandag geniet, tesame met die akademiese en administratiewe aspekte wat met die saamstel van die model gepaardgaan. Uitdagings ten opsigte van lewering, sowel as aanbevelings ten opsigte van die model, is voorsien. Die studie is uitgevoer om ‘n bydrae te lewer tot die voorgesette doeltreffende en doelmatige implementering van die VPO-stelsel vir arbeidsterapeute in Suid-Afrika, deur die identifisering van die VPO-behoeftes van arbeidsterapeute en eindelik om deur onderwys steun te verleen aan gesondheidsorg in Suid-Afrika. Die studie sou ook kon dien as rigtinggewend vir hoëronderwysinstellings, aangesien nie alle voorgraadse programme en leerplanne noodwendig op volwasse-onderwysbeginsels geskoei is nie. Dit mag veral in professionele dissiplines die geval wees dat die bevindinge van die studie sou kon dien om die leemtes in hierdie verband aan te vul. Die navorser is van mening dat die navorsing ‘n bydrae gelewer het tot nuwe kennis. Die gaping wat geïdentifiseer is, is deur die ontwikkeling van die model oorbrug. Die deeglik begronde navorsingsbenadering en metodologie het die gehalte, betroubaarheid en geldigheid van die navorsing verseker. Die voltooide navorsing kan die grondslag vir ‘n verdere navorsingsagenda vorm. Die inwerkingstelling van die model sal VPO-verskaffers aanmoedig om leeraktiwiteite te voorsien wat ooreenstem met volwasse-onderwysbeginsels en groter leerderbetrokkenheid, met die oog daarop om nie net nuwe inligting in te win of kennis by te werk nie, maar ook om vaardigheid en eindelik die prestasie van die professionele gesondheidswerker te verbeter, met ‘n eindvoordeel aan die pasiënt.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2011
Keywords: Adult education; Adult education perspective; Adult education principles; Continuing Professional Development (CPD); Delphi process; Mixed-methods design; Model for CPD; Needs analysis; Occupational therapy; Adult education -- South Africa; Occupational therapists -- Vocational guidance; Occupational therapy -- Study and teaching (Continuing education)